2019
DOI: 10.3390/en12112051
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Shoot Size and Genotype on Energy Properties of Poplar Biomass in Short Rotation Crops

Abstract: Eight poplar genotypes grown in a short rotation forest plantation established in an acid soil in South Europe were sampled at the age of 7 years to determine the energy properties regarding thermochemical conversion. The goal was to address the effect of selection of genotypes or shoot size at harvest on the energy quality of biomass. Between 34 and 50 biomass samples were obtained for each genotype: three disks were systematically sampled along the stem and were pooled together with a subsample of leafless b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 47 publications
(51 reference statements)
1
13
0
Order By: Relevance
“…In Spain, several studies have addressed the characterization of poplar biomass for thermal use [148,231,292,293] as biofuels [294][295][296][297] or for new bioproducts [298,299]. The lower heating value, which is used to calculated the available energy, is usually around 18-20 MJ kg −1 in poplar wood on a dry basis [300,301].…”
Section: Biomass Characterizationmentioning
confidence: 99%
See 2 more Smart Citations
“…In Spain, several studies have addressed the characterization of poplar biomass for thermal use [148,231,292,293] as biofuels [294][295][296][297] or for new bioproducts [298,299]. The lower heating value, which is used to calculated the available energy, is usually around 18-20 MJ kg −1 in poplar wood on a dry basis [300,301].…”
Section: Biomass Characterizationmentioning
confidence: 99%
“…The humidity content can be as high as 48-50% at winter harvesting [231,303], but poplar biomass has shown a good ability for air drying [303]. The specific density is known to be low [304][305][306][307], thus deriving in low bulk density chips (150-260 kg m −3 , [231]), corresponding to low energy densities. Densification to produce pellets is therefore an option.…”
Section: Biomass Characterizationmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, Lerma-Arce et al [14] found values of 0.46% for logs with diameters greater than 20 cm of Pinus pinaster with bark. Eimil-Fraga et al [100] and Werkelin et al [101] mentioned that the basal diameter has a significant effect on the ash content mainly because the bark content increases with smaller diameters [38]. In addition, Miranda et al [40] reported for Quercus pyrenaica branches that lower diameters correspond to higher ash content.…”
Section: Immediate Analysismentioning
confidence: 99%
“…It is an important tree species in many European countries. Populus × euramericana is characterized by rapid growth rates, ease of clonal propagation, coppice regeneration, high biomass production and carbon sequestration, potential for phytoremediation, and suitability for multiple industrial uses, e.g., sawn timber, veneers, and fuelwood [1][2][3].…”
Section: Introductionmentioning
confidence: 99%